How does gender equality affect reproductive decision-making amongst married Singaporeans? - Chia, Stephanie Shu Ying. (2013)
In recent talks (2011) to the Committee on Elimination of Discrimination against Women, Singapore cited gender-equality as a key factor in contributing towards socio-economic growth. However, gender equality is not held across all social institutions especially in the realm of the workplace and at home. Social policies as well do not seem to address this issue.In order to maintain and continue the current drive of the economy, the Singapore government has been trying to maintain its labour workforce size as current fertility rates are at an all time low even amongst developed countries in the US and Western Europe. However, despite the generous investments of subsidies and policies encouraging production via co-payments, fertility rates still remain at an all time low.This paper sets out to explore if the inconsistency in gender equality affects reproductive decision making negatively, thus contributing to the declining fertility rates despite governments’ efforts to address this issue via their policies.